When traffic light management prefigures mobility choices: the strategic challenges of a technical tool - Céline Brandeleer; Thomas Ermans (Brussels Studies)
This article opens the black box of the remote controlled traffic light system used by public transport in Brussels. This technical device redistributes the temporal sharing of space in favour of public transport, which allows the constant erosion of the commercial speed faced by the Société de transports intercommunaux de Bruxelles (STIB) to be halted, thus cutting back on operational costs. Our objective is to make sense of this technical device and to highlight the underlying political challenges in terms of the management of space. At the heart of discussions on remote controlled traffic lights is of course the question of the respective role of public transport and cars in the context of a very high level of road congestion. We also wish to emphasise the relatively invisible work of the administration (in this case Bruxelles Mobilité) in its capacity to create compromises – with their advantages and disadvantages – so that a project is able to function within the Brussels “ecosystem”.